(3aJM GdbOhS GdeZdbGJ GdbGehSs - (3CHh RjO , YHO GdQMef Hf YHO GdYRjR GdeZQHj GdJGOdi GdeOfj GdYeQis; (3eMeO Hf jYbhH Hf eMeO Hf EHQGgje Hf YeQ, CHh WGgQ, eLO GdOjf GdTjQGRj GdajQhRBHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeJaVd YdjfG Hcd aVjdI hGdeSOi EdjfG Hcd YWjI LRjdI hGdTcQ dg Ydi eG ChdGfG ef GdfYe , hhbGfG ef Gdfbe s
(3BNQgG (B:s
(3hGdOKGQ hGdZTGA hGdZWGA hGdYaGU hGddg Gdehab ddUhGH JeJ GdbhGYO HMeO Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B118s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs